Preparation method and application of oil-water separation film

After the tetrateate hydrolyzed and sorne is treated, the electrostatic spinning wire with polystumin is combined to prepare a highly efficient and biodegradable oil -water separation film to solve the problem of low existing membrane efficiency and non -degradable problems. It has achieved the degradation effect of high -efficiency oil and water separation and environmental friendliness.

CN119368007AInactive Publication Date: 2025-01-28ORINKO ADVANCED PLASTICS CO LTD +1

Patent Information

Application Number
CN202411325103.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing oil-water separation membrane has low filtration efficiency and is not biodegradable, resulting in environmental pollution and ecological hazards.

Method used

By hydrolyzing and annealing treatment of titanate titanate, a hydroxyl -based titanium dioxide nanoparticles are obtained, and a silicerine titanium titanium dioxide nanoparticles are formed through ahrilane treatment and modified modification. film.

Benefits of technology

This oil and water separation film not only has efficient oil and water separation characteristics, but also can naturally degrade naturally after the service life is over to reduce environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368007A_ABST
    Figure CN119368007A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an oil-water separation film, and belongs to the technical field of oil-water separation.The preparation method comprises the following steps that 1, tetrabutyl titanate is subjected to hydrolytic annealing treatment, and titanium dioxide nanoparticles with the surfaces rich in hydroxyl are obtained; step 2, modifying the titanium dioxide nano-particles rich in hydroxyl groups to obtain silanized titanium dioxide nano-particles; 3, the silanized titanium dioxide nanoparticles are placed in a mixed solvent, ultrasonic dispersion is carried out for 10 min, a homogeneous precursor solution is obtained, polylactic acid is added, stirring dispersion is carried out until the solution is transparent, a spinning solution is obtained, electrostatic spinning is carried out on the spinning solution, and the oil-water separation film is obtained.The obtained oil-water separation film has the excellent oil-water separation characteristic. In addition, the oil-water separation membrane can effectively purify oil-containing wastewater, and can be naturally degraded after the service life is ended, so that the negative influence on the environment is reduced to the greatest extent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oil-water separation, and in particular relates to a preparation method of an oil-water separation film and application thereof. Background Art

[0002] Offshore crude oil spills and industrial oily waste discharges pose a serious threat to ecosystems and human health, while severely damaging the global water-food-energy chain. To meet this challenge, oil-water separation technology based on superhydrophilic membranes has been widely used to treat oily wastewater. The separation principle of this technology relies on the superhydrophilicity of the material, which allows water to pass smoothly through the pore structure inside the material and form a hydration layer on the surface, thereby effectively preventing oil from penetrating. In addition, the capillary force generated by the microporous structure and high specific surface area of ​​the material can also promote the demulsification of the emulsion, which helps to achieve oil-water separation.

[0003] However, most of the existing oil-water separation membranes are derived from fossil resources, and their waste is often disposed of by landfill or incineration, which may cause secondary pollution and is not conducive to the sustainable development of the ecological environment. Therefore, it is particularly important to develop an oil-water separation membrane with biodegradable properties. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing an oil-water separation membrane and its application, which overcomes the shortcomings of the current oil-water separation membrane, such as low filtration efficiency and non-biodegradability.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing an oil-water separation film comprises the following steps:

[0007] Step 1: hydrolyzing and annealing tetrabutyl titanate to obtain titanium dioxide nanoparticles with a rich surface hydroxyl group;

[0008] Step 2: modifying the above hydroxyl-rich titanium dioxide nanoparticles to obtain silanized titanium dioxide nanoparticles;

[0009] Step 3: ultrasonically disperse the silanized titanium dioxide nanoparticles in a mixed solvent for 10 minutes to obtain a homogeneous precursor solution, add polylactic acid, stir and disperse until transparent to obtain a spinning solution, and electrospin the spinning solution to obtain an oil-water separation film.

[0010] Furthermore, the specific preparation steps of titanium dioxide nanoparticles rich in hydroxyl groups on the surface are as follows:

[0011] Deionized water and tetrabutyl titanate are mixed in a ratio of 1-2 g: 1-10 mL, stirred at low temperature of 4° C. for 2 h, centrifuged and precipitated, and treated at 80-120° C. for 8 h to obtain hydroxyl-rich titanium dioxide nanoparticles.

[0012] Furthermore, the specific preparation steps of silanized titanium dioxide nanoparticles are as follows:

[0013] Hydroxyl-rich titanium dioxide nanoparticles, ionized water and silane coupling agent were mixed in a ratio of 2g:5mL:5mL, and then placed in a vacuum sealed container. The reaction was continued at 100-150°C in vacuum (less than 0.1Pa) for 2 hours. After the reaction was completed, it was washed with anhydrous ethanol, centrifuged and freeze-dried to obtain silanized titanium dioxide nanoparticles.

[0014] Furthermore, the silane coupling agent is any one or more of methyltrimethoxysilane, vinyltrimethoxysilane, γ-aminopropyltrimethoxysilane, trimethoxy(propyl)silane, trimethylchlorosilane, tetraethyl orthosilicate and propyltrimethoxysilane.

[0015] Furthermore, the mass ratio of the silanized titanium dioxide nanoparticles, the polylactic acid and the mixed solvent is 0.05-0.3:1-3:10.

[0016] Furthermore, the mixed solvent is composed of solvent A and solvent B in a mass ratio of 7-10:1.5-4.5, solvent A is chloroform or dichloromethane, and solvent B is any one of dimethylformamide, ethyl acetate and formic acid.

[0017] Furthermore, the electrospinning voltage was 15 KV, the spinning flow rate was 1.0 mL / h, and the spinning distance was 15 cm.

[0018] Furthermore, the oil-water separation film prepared as described above is applied in the field of oil-water separation.

[0019] Beneficial effects of the present invention:

[0020] (1) The present invention uses polylactic acid as the oil-water separation membrane matrix, mixes it with a silanized titanium dioxide nanoparticle solution to form a spinning solution, and prepares an oil-water separation membrane through an electrostatic spinning process. This film can not only effectively purify oily wastewater, but also naturally degrade after the end of its service life, thereby minimizing the negative impact on the environment. This technology is expected to be widely used in the treatment of oily wastewater generated by petrochemical, metallurgical, textile, food industries, etc., as well as in urban sewage treatment, crude oil spill emergency response, ship transportation, oil and gas production, etc., to contribute to the realization of efficient oil-water separation and environmental protection.

[0021] (2) The method of the present invention achieves uniform and efficient compounding of polylactic acid and nanoparticles by introducing silanized titanium dioxide nanoparticles, constructs a multi-level structure, and enables the prepared oil-water separation membrane to have stable and excellent oil-water separation properties.

[0022] (3) The silane functional groups on the surface of the titanium dioxide nanoparticles of the present invention can improve the interfacial compatibility between polylactic acid and the nanoparticles, so that a multi-level network structure is formed inside the oil-water separation membrane, and the prepared oil-water separation membrane has excellent hydrophobic properties.

[0023] (4) The oil-water separation membrane of the present invention is firstly obtained by efficiently compounding silanized titanium dioxide nanoparticles with polylactic acid and then by an electrospinning process. Nano-sized silanized titanium dioxide is homogeneously mixed with polylactic acid, and the prepared oil-water separation membrane has excellent oil-water separation properties. In addition, the oil-water separation membrane can effectively purify oily wastewater and can also naturally degrade after the end of its service life, thereby minimizing the negative impact on the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The present invention will be further described below in conjunction with the accompanying drawings.

[0025] Figure 1 This is a finished product picture of the oil-water separation film obtained by the preparation method of Example 1 of the present invention;

[0026] Figure 2 It is a scanning electron microscope image of the oil-water separation film obtained by the preparation methods of Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention;

[0027] Figure 3 The optical photographs of the hydrophilic contact angles of the oil-water separation films obtained by the preparation methods of Example 1 and Comparative Example 1 of the present invention;

[0028] Figure 4 The optical photographs of the lipophilic contact angles of the oil-water separation films obtained by the preparation methods of Example 1 and Comparative Example 1 of the present invention;

[0029] Figure 5 is a graph showing the relationship between the hydrophilic contact angle of the oil-water separation film obtained by the preparation methods of Example 1 of the present invention and Comparative Example 1 and time;

[0030] Figure 6 is a graph showing the relationship between the lipophilic contact angle of the oil-water separation film obtained by the preparation methods of Example 1 of the present invention and Comparative Example 1 and time;

[0031] Figure 7 is a schematic diagram of an oil-water separation device of the present invention;

[0032] Figure 8It is the oil-water separation flow diagram of the oil-water separation membrane of Comparative Example 1, Example 1, Example 2 and Example 3 of the present invention. DETAILED DESCRIPTION

[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] A method for preparing an oil-water separation film comprises the following steps:

[0035] Step 1: hydrolyzing and annealing tetrabutyl titanate to obtain titanium dioxide nanoparticles with a rich surface hydroxyl group;

[0036] Step 2: modifying the above hydroxyl-rich titanium dioxide nanoparticles to obtain silanized titanium dioxide nanoparticles;

[0037] Step 3: ultrasonically disperse the silanized titanium dioxide nanoparticles in a mixed solvent for 10 minutes to obtain a homogeneous precursor solution, add polylactic acid, stir and disperse until transparent to obtain a spinning solution, and electrospin the spinning solution to obtain an oil-water separation film.

[0038] The specific preparation steps of titanium dioxide nanoparticles rich in hydroxyl groups on the surface are as follows:

[0039] Deionized water and tetrabutyl titanate are mixed in a ratio of 1-2 g: 1-10 mL, stirred at low temperature of 4° C. for 2 h, centrifuged and precipitated, and treated at 80-120° C. for 8 h to obtain hydroxyl-rich titanium dioxide nanoparticles.

[0040] The specific preparation steps of silanized titanium dioxide nanoparticles are as follows:

[0041] Hydroxyl-rich titanium dioxide nanoparticles, ionized water and silane coupling agent were mixed in a ratio of 2g:5mL:5mL, and then placed in a vacuum sealed container. The reaction was continued at 100-150°C in vacuum (less than 0.1Pa) for 2 hours. After the reaction was completed, it was washed with anhydrous ethanol, centrifuged and freeze-dried to obtain silanized titanium dioxide nanoparticles.

[0042] The silane coupling agent is any one or more of methyltrimethoxysilane, vinyltrimethoxysilane, γ-aminopropyltrimethoxysilane, trimethoxy(propyl)silane, trimethylchlorosilane, tetraethyl orthosilicate and propyltrimethoxysilane.

[0043] The mass ratio of silanized titanium dioxide nanoparticles, polylactic acid and mixed solvent is 0.05-0.3:1-3:10.

[0044] The mixed solvent is composed of solvent A and solvent B in a mass ratio of 7-10:1.5-4.5, solvent A is chloroform or dichloromethane, and solvent B is any one of dimethylformamide, ethyl acetate and formic acid.

[0045] The electrospinning voltage was 15 KV, the spinning flow rate was 1.0 mL / h, and the spinning distance was 15 cm.

[0046] Example 1

[0047] A method for preparing an oil-water separation film comprises the following steps:

[0048] Step 1: 5 g of tetrabutyl titanate was added dropwise into 5 mL of deionized water, stirred at low temperature of 4 ° C for 2 h, centrifuged and precipitated, and annealed in an oven at 80 ° C for 8 h to obtain hydroxyl-rich titanium dioxide nanoparticles;

[0049] Step 2: Take 2 g of the hydroxyl-rich titanium dioxide nanoparticles obtained in step 1, 5 mL of deionized water, and 5 mL of deionized water, place them in a vacuum sealed container, treat them at 100° C. in vacuum (less than 0.1 Pa) for 2 h, then wash them with anhydrous ethanol, centrifuge them, and freeze-dry them to obtain silanized titanium dioxide nanoparticles;

[0050] Step 3: Add 0.05 g of the above-mentioned silanized titanium dioxide nanoparticles to 10 mL of a mixed solvent consisting of chloroform and dimethylformamide in a mass ratio of 7:3, and ultrasonically disperse for 10 minutes to obtain a homogeneous precursor solution. Then add 1 g of polylactic acid and stir and disperse until transparent to obtain a spinning solution. The spinning solution is electrospun at a voltage of 15 KV, a spinning flow rate of 1.0 mL / h, and a spinning distance of 15 cm to obtain an oil-water separation film.

[0051] The finished product of the oil-water separation membrane obtained in Example 1 is shown in FIG. Figure 1 As shown by Figure 1 It can be seen that the membrane can be prepared on a large scale and still has good integrity even after continuous folding.

[0052] Example 2

[0053] A method for preparing an oil-water separation film comprises the following steps:

[0054] Step 1: 1.5 g of tetrabutyl titanate was added dropwise into 8 mL of deionized water, stirred at low temperature of 4 ° C for 2 h, centrifuged and precipitated, and annealed in an oven at 100 ° C for 8 h to obtain hydroxyl-rich titanium dioxide nanoparticles;

[0055] Step 2: Take 2 g of the hydroxyl-rich titanium dioxide nanoparticles obtained in step 1, 5 mL of deionized water, and 5 mL of deionized water, place them in a vacuum sealed container, treat them at 125° C. in vacuum (less than 0.1 Pa) for 2 h, then wash them with anhydrous ethanol, centrifuge them, and freeze-dry them to obtain silanized titanium dioxide nanoparticles;

[0056] Step 3: Add 0.2 g of the above-mentioned silanized titanium dioxide nanoparticles to 10 mL of a mixed solvent consisting of chloroform and ethyl acetate in a mass ratio of 7:3, and ultrasonically disperse for 10 minutes to obtain a homogeneous precursor solution. Then add 2 g of polylactic acid and stir and disperse until transparent to obtain a spinning solution. The spinning solution is electrospun at a voltage of 15 KV, a spinning flow rate of 1.0 mL / h, and a spinning distance of 15 cm to obtain an oil-water separation film.

[0057] Example 3

[0058] A method for preparing an oil-water separation film comprises the following steps:

[0059] Step 1: 2 g of tetrabutyl titanate was added dropwise into 10 mL of deionized water, stirred at low temperature of 4 ° C for 2 h, centrifuged and precipitated, and annealed in an oven at 120 ° C for 8 h to obtain hydroxyl-rich titanium dioxide nanoparticles;

[0060] Step 2: Take 2 g of the hydroxyl-rich titanium dioxide nanoparticles obtained in step 1, 5 mL of deionized water, and 5 mL of deionized water, place them in a vacuum sealed container, treat them at 150° C. in vacuum (less than 0.1 Pa) for 2 h, then wash them with anhydrous ethanol, centrifuge them, and freeze-dry them to obtain silanized titanium dioxide nanoparticles;

[0061] Step 3: Add 0.3 g of the above-mentioned silanized titanium dioxide nanoparticles to 10 mL of a mixed solvent consisting of dichloromethane and ethyl acetate in a mass ratio of 7:3, and ultrasonically disperse for 10 minutes to obtain a homogeneous precursor solution. Then add 3 g of polylactic acid and stir and disperse until transparent to obtain a spinning solution. The spinning solution is electrospun at a voltage of 15 KV, a spinning flow rate of 1.0 mL / h, and a spinning distance of 15 cm to obtain an oil-water separation film.

[0062] Comparative Example 1

[0063] A method for preparing an oil-water separation film comprises the following steps:

[0064] Step 1: 5 g of tetrabutyl titanate was added dropwise into 5 mL of deionized water, stirred at low temperature of 4 ° C for 2 h, centrifuged and precipitated, and annealed in an oven at 80 ° C for 8 h to obtain hydroxyl-rich titanium dioxide nanoparticles;

[0065] Step 2: Add 0.05 g of hydroxyl-rich titanium dioxide nanoparticles to 10 mL of a mixed solvent consisting of chloroform and dimethylformamide in a mass ratio of 7:3, and ultrasonically disperse for 10 minutes to obtain a homogeneous precursor solution. Add 1 g of polylactic acid and stir and disperse until transparent to obtain a spinning solution. The spinning solution is electrospun at a voltage of 15 KV, a spinning flow rate of 1.0 mL / h, and a spinning distance of 15 cm to obtain an oil-water separation film.

[0066] The oil-water separation membranes obtained by the preparation methods described in Example 1, Example 2, Example 3 and Comparative Example 1 were observed using a scanning electron microscope, wherein: Figure 2 a is a scanning electron microscope image of the oil-water separation film of comparative example 1, Figure 2 b is a scanning electron microscope image of the oil-water separation membrane of Example 1, Figure 2 c is a scanning electron microscope image of the oil-water separation film of Example 2, Figure 2 c is a scanning electron microscope image of the oil-water separation film of Example 3, Figure 2 It can be seen that with the addition of silanized titanium dioxide nanoparticles, Example 3 shows richer porosity than Example 2 and Example 1. This is because the silane functional groups on the silanized titanium dioxide nanoparticles can build an effective cross-linked network system inside the system, enriching the multi-level pore structure of the material. Since Comparative Example 1 was not silanized, the interface compatibility with polylactic acid was poor.

[0067] The hydrophilic contact angle test was performed on the oil-water separation film obtained by the preparation method described in Example 1 and Comparative Example 1, wherein: Figure 3 a is the hydrophilic contact angle measurement image of comparative example 1, Figure 3 b is the hydrophilic contact angle measurement image of Example 1. The results show that the contact angle of Example 1 is greater than that of Comparative Example 1, indicating that the hydrophobicity of Example 1 is higher than that of Comparative Example 1. This phenomenon indicates that the introduction of silanized titanium dioxide nanoparticles in Example 1 leads to a decrease in the hydrophilicity of the oil-water separation membrane. Specifically, a larger hydrophilic contact angle means that the surface of the example has poor wettability to aqueous liquids, and the surface energy is reduced, thereby reducing the wettability of water. In contrast, the smaller hydrophilic contact angle of the membrane of Comparative Example 1 indicates that its surface has a stronger wettability to water.

[0068] The oil-water separation film obtained by the preparation method described in Example 1 and Comparative Example 1 was tested for its lipophilic contact angle, wherein: Figure 4 a is the lipophilic contact angle measurement image of comparative example 1, Figure 4b is the lipophilic contact angle measurement image of Example 1. The results show that the lipophilic contact angle of Example 1 is smaller, while the lipophilic contact angle of Comparative Example 1 is larger. This shows that Example 1 has stronger lipophilicity, while Comparative Example 1 shows relatively strong oleophobicity. Specifically, the smaller lipophilic contact angle indicates that the surface of Example 1 has better wettability to oily liquids, higher surface energy, and is conducive to the infiltration of oily liquids. This shows that the silanized titanium dioxide nanoparticles improve the lipophilicity of the oil-water separation membrane.

[0069] The hydrophilic contact angle stability test was performed on the oil-water separation film obtained by the preparation method described in Example 1 and Comparative Example 1. Figure 5 As shown, Figure 5 The relationship between the hydrophilic contact angle and time of Comparative Example 1 and Example 1 is shown, and the results show that both Comparative Example 1 and Example 1 exhibit stable hydrophobicity.

[0070] The oil-water separation film prepared by the preparation method described in Example 1 and Comparative Example 1 was subjected to a lipophilic contact angle stability test. Figure 6 As shown, Figure 6 The relationship between the lipophilic contact angle and time of Comparative Example 1 and Example 1 is shown. The results show that Comparative Example 1 exhibits slower and more stable oil absorption than Example 1.

[0071] The oil-water separation test was performed on the oil-water separation membrane obtained by the preparation method described in Example 1 and Comparative Example 1. Figure 7 A schematic diagram of the oil-water separation device is shown. In the experiment, 10 mL of n-hexadecane was mixed with 30 mL of deionized water, with an oil-water volume ratio of 1:3. Sudan III dye was added to n-hexadecane for dyeing, while deionized water remained undyed.

[0072] Figure 8 The oil-water separation flow diagrams of Comparative Example 1, Example 1, Example 2 and Example 3 are shown, wherein the n-hexadecane flux of the oil-water separation membrane is obtained according to the membrane flux calculation formula:

[0073] Product (m 2 ), t is the operation time (h).

[0075] It can be seen that compared with Comparative Example 1, Example 1 presents a more obvious oil-water separation membrane flux, wherein with the addition of silanized titanium dioxide nanoparticles, the oil-water separation membrane flux gradually increases.

[0076] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0077] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an oil-water separation film, characterized in that: The steps include: Step 1: hydrolyzing and annealing tetrabutyl titanate to obtain titanium dioxide nanoparticles with a rich surface hydroxyl group; Step 2: modifying the above hydroxyl-rich titanium dioxide nanoparticles to obtain silanized titanium dioxide nanoparticles; Step 3: ultrasonically disperse the silanized titanium dioxide nanoparticles in a mixed solvent for 10 minutes to obtain a homogeneous precursor solution, add polylactic acid, stir and disperse until transparent to obtain a spinning solution, and electrospin the spinning solution to obtain an oil-water separation film.

2. The method for preparing an oil-water separation film according to claim 1, characterized in that: The specific preparation steps of silanized titanium dioxide nanoparticles are as follows: Hydroxyl-rich titanium dioxide nanoparticles, ionized water and silane coupling agent were mixed in a ratio of 2g:5mL:5mL, and then placed in a vacuum sealed container. The reaction was continued at 100-150°C for 2 hours. After the reaction was completed, the mixture was washed with anhydrous ethanol, centrifuged and freeze-dried to obtain silanized titanium dioxide nanoparticles.

3. The method for preparing an oil-water separation film according to claim 2, characterized in that: The silane coupling agent is any one or more of methyltrimethoxysilane, vinyltrimethoxysilane, γ-aminopropyltrimethoxysilane, trimethoxy(propyl)silane, trimethylchlorosilane, tetraethyl orthosilicate and propyltrimethoxysilane.

4. The method for preparing an oil-water separation film according to claim 2, characterized in that: The mass ratio of silanized titanium dioxide nanoparticles, polylactic acid and mixed solvent is 0.05-0.3:1-3:

10.

5. The method for preparing an oil-water separation film according to claim 2, characterized in that: The mixed solvent is composed of solvent A and solvent B in a mass ratio of 7-10:1.5-4.5, solvent A is chloroform or dichloromethane, and solvent B is any one of dimethylformamide, ethyl acetate and formic acid.

6. The method for preparing an oil-water separation film according to claim 1, characterized in that: The electrospinning voltage was 15 KV, the spinning flow rate was 1.0 mL / h, and the spinning distance was 15 cm.

7. A method for preparing an oil-water separation membrane according to any one of claims 1 to 6, characterized in that: The prepared film is used in the field of oil-water separation.

Citation Information

Patent Citations

  • Fiber membrane for water-in-oil emulsion separation and preparation method thereof

    CN115591412A

  • Preparation method and application of super-hydrophobic polylactic acid nanofiber membrane

    CN116036876A

  • Solvent-resistant hydrophilic stereocomplex polylactic acid oil-water separation membrane and preparation method thereof

    CN116764464A

  • Waterproof moisture-permeable nanofiber antibacterial film and preparation method thereof

    CN117107432A

  • Membrane made of a nanostructured material

    US20100233812A1

Cited By

  • PLA / CDA (at) PDA-BC composite membrane for oil-water separation and preparation method and application thereof

    CN121060330A